(untitled) (PANGEEA, 2025)
Rural areas remain a major part of Europe’s land area. For several reasons, the EU wants to see sustainable development. Several European funds are therefore intended to support activities, particularly economic activities, in rural areas. Thus, motivated by such European policy, we considered it appropriate to carry out research at the level of a commune with an important level of living and economic development. We focused our attention on the commune of Cenad in Timis county, a commune on the western border with Hungary. In the methodological approach we used different types of documents and a range of research methods (participatory observation, case study, document analysis, interviews) to highlight the level of economic and social development achieved by the community of Cenad. Even if the inhabitants are mostly satisfied with what has been achieved in their community, even if unemployment is very low and does not put pressure on the social welfare system, we have nevertheless identified certain directions of sustainable development of the locality and implicitly of the community that can be beneficial for all, inhabitants, or tourists.